Routes of Infection, Viremia, and Liver Disease in Blood Donors Found to Have Hepatitis C Virus Infection - Cathy Conry‐Cantilena; Mark VanRaden; Joan Gibble; Jacqueline C. Melpolder; A. Obaid Shakil; L Viladomiu; Ling Cheung; A DIBISCEGLIE; Jay H. Hoofnagle; J W Shih; Richard A. Kaslow; Paul M. Ness; et al. (1996)
For many people infected with the hepatitis C virus (HCV), the route of exposure, risk of transmission, and severity of associated liver disease are unknown. We studied these variables in people who donated blood voluntarily.